(NgENRIH(B.(N{@TC(B. (No^ERK VIZNI I TWOR^ESTWAs (NMONOGRAFIQs - (Nw(B.(N{TEJNGRARDs ((NmOSKWAs (NmUZYKAs, 1980)
(Nw KNIGE RASSMATRIWA@TSQ OSOBENNOSTI TWOR^ESTWA KOMPOZITORA W g(B.(N{@TCA(B, (NRASKRYWAETSQ ISTORI^ESKOE ZNA^ENIE EGO NASLEDIQ(B.s
Keywords: (NMONOGRAFIQs